1998
DOI: 10.1097/00005344-199800001-00003
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of Asn-632 and Asn-651 Is Important for Functional Expression of Endothelin-Converting Enzyme-1

Abstract: It has been shown previously that N-glycosylation of Asn-144 and/or Asn-627 is important for functional expression of neutral endopeptidase-24.11 (NEP). All glycosylation sites of NEP are conserved within endothelin-converting enzyme-1 (ECE-1). In the present study we investigated the importance of proper glycosylation for the biologic function of ECE-1. We show that the double mutation of Asn-632 and Asn-651 leads to expression of an enzymatically inactive ECE-1 protein. In contrast, the single mutation of ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1999
1999
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In agreement with this conclusion, deglycosylation of purified ECE-1 did not significantly alter its enzyme activity (42). Mutating two of ECE-1 glycosylation sites is, however, enough to render the enzyme inactive (43), which is expected considering the importance of glycosylation for proper protein folding in the secretory pathway (for review see (44). Our data thus suggest that molecular chaperones can efficiently compensate for the lack of glycosylation and promote proper folding of ECE-1sv in the cytosol.…”
Section: Discussionsupporting
confidence: 72%
“…In agreement with this conclusion, deglycosylation of purified ECE-1 did not significantly alter its enzyme activity (42). Mutating two of ECE-1 glycosylation sites is, however, enough to render the enzyme inactive (43), which is expected considering the importance of glycosylation for proper protein folding in the secretory pathway (for review see (44). Our data thus suggest that molecular chaperones can efficiently compensate for the lack of glycosylation and promote proper folding of ECE-1sv in the cytosol.…”
Section: Discussionsupporting
confidence: 72%
“…Ten potential glycosylation signals are present in Lom ECE, suggesting that Lom ECE, like mammalian ECE, is a highly glycosylated protein with a higher molecular weight than calculated from its predicted residue masses alone (Shimada et al ., 1994). Among these glycosylation signals in Lom ECE, Asn 589 and Asn 608 are found, which are proven to be important for the functional expression of mammalian ECE‐1 (Nelboeck et al ., 1998). The putative zinc ligand Glu 624, which is located 61 residues downstream from the active site compares with a 61 AA separation in mammalian ECE (Shimada et al ., 1995a,b), in contrast to mammalian NEP which possesses a 64 residue separation (Hooper et al ., 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Among these glycosylation signals in Lom ECE, Asn 589 and Asn 608 are found, which are proven to be important for the functional expression of mammalian ECE‐1 (Nelboeck et al ., 1998). The putative zinc ligand Glu 624, which is located 61 residues downstream from the active site compares with a 61 AA separation in mammalian ECE (Shimada et al ., 1995a,b), in contrast to mammalian NEP which possesses a 64 residue separation (Hooper et al ., 1994). The CEVW sequence, critical for proper enzyme maturation and enzyme activity (MacLeod et al ., 2001), conserved among all mammalian ECE sequences, is present in Lom ECE.…”
Section: Discussionmentioning
confidence: 99%
“…Single mutations of the glycosylated Asn632 and Asn651 of the metalloprotease endothelin-converting enzyme had no effect, while the double mutant was completely inactive [109]. A series of sequon mutants of mouse meprin-α showed that six out of ten N -glycans are critical for catalysis [110].…”
Section: Effects Of Glycosylation On Proteasesmentioning
confidence: 99%